Factors contributing to customer satisfaction - Ng, Chor Hoon (2015)
Customer satisfaction, as the name implies, is the extent to which a firm's products or services meet the expectations of its customers. With more intense competition and highly-demanding customers, coupled with advancement in technology, large firms are not always the ultimate successful competitors. Smaller firms, which are ill-equipped to win a price war, can still capture the market if they can gain a competitive edge by making the customers satisfied. Trying to compete solely on the basis of product or price is insufficient. Customers also want to be treated well and do repeat business with places that emphasize service. There are many factors affecting customer satisfaction. For firms in the service industries, one such dominant factor is the quality of customer service. Service differentiation is a viable marketing strategy that works within these industries. The differentiation has to be obvious and of value to the customers. While maximizing customer satisfaction may require additional costs to be incurred, the bottom line is that keeping customer satisfied is crucial to the firm's long-run profitability and viability.